Angkasawan lifting Malaysian dreams - Abd Razak, Dzulkifli (2007)
IN the 1960s, President John F. Kennedy poured millions of dollars into funding a space programme to land the first man on the Moon by 1970. In his famous words: "I believe that this nation should commit itself to achieving the goal, before this decade is out, of landing a man on the Moon and returning him safely to Earth." It was the Cold War and the Soviet Union, which launched its first satellite, the Sputnik, into space in 1957, and the United States were involved in an intense space race.